Model Rantai Pasokan Agile untuk Komoditas Sayuran Segar - Nadia Yefika; Rika Ampuh Hadiguna (UIN Sultan Syarif Kasim Riau, 2016)
Fresh vegetables are commodities that sold on traditional markets especially in rural region inIndonesia. Fresh vegetables sold on the traditional markets will be distributed to retailers and wholesalers.The study is study and build supply chain model of fresh vegetables from Koto Baru, Agam to retailers andwholesalers in Pekanbaru. The problem is fulfil the demand in terms of both quantity and quality of freshvegetables. Purpose of the study was to build supply chain that provide benefits for the actors in thesupply chain, namely farmers and collectors. Model is formulated with deterministic static situation.Objective function is maximization of revenue in the supply chain system. The variables of model is priceof vegetables at the farmers and collectors. Analysis is conducted by comparing the three scenarios.Keywords: fresh vegetables, rantai pasokan, agile, deterministic, scenario